Analisis Faktor-Faktor yang Mempengaruhi Kebijakan Hutang pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Nurwani Nurwani (Jurnal Riset AKuntansi dan Bisnis, 2020)
The purpose of this research was to examine the influence and analyze of profitability, institutional ownership, managerial ownership, dividend policy, and investment opportunity set as on debt policy partially and simultaneously. The population of this research was 168 manufacture companies listed in the Indonesia Stock Exchange in the period of 2013-2018 and samples taken by using purposive sampling technique. The data were processed by using multiple linear regression analysis. The result of the research showed that first, profitability had influence negative and insignificant on dividend policy; secondly, institutional ownership had influence positive and insignificant on dividend policy; thirdly, managerial ownership had influence negative and significant on dividend policy; fourthly, dividend policy had influence positive and insignificant on dividend policy; fifthly, investment opportunity set had influence positive and insignificant on dividend policy; and sixthly, profitability, institutional ownership, managerial ownership, dividend policy, and investment opportunity set as on debt policy simultaneously.